Case report: Mature extragonadal teratoma at the proximal part of the tail in a kitten - Sirivisoot, Sirintra; Siripara, Naklop; Arya, Nlin; Techangamsuwan, Somporn; Rungsipipat, Anudep; Kasantikul, Tanit (Frontiers in Veterinary Science, 2022)
An 8-month-old, intact male, domestic shorthair cat was referred for a mass on the proximal ventral part of the tail which had been found since the animal was born, and due to the presence of a linear fissure with rows of ectopic teeth, the veterinarian suspected that the mass had recently ruptured. Tail amputation was elected and the entire mass was successfully surgically excised. From the gross examination, this mass had an open cyst-like structure with a prominent area composed of hair, teeth, and bone. Histopathology revealed two components of germinal layers including hair follicles, adnexal tissue, neural tissue, teeth, muscle, fat, bone, and lymphatic vessels. The histopathological diagnosis was consistent to mature teratoma. Although, complete excision could not be definitively confirmed histologically, this kitten is currently well and has not developed any recurrent mass at the surgical site after two years of post-operation.